Study of the feasibility of adding probiotics and prebiotics in gelatin for the development of a functional food (Agroindustria, Sociedad y Ambiente, 2016)
The study is based on the evaluation of the feasibility of using gelatin as a base ingredient in the manufacture of a functional food, which was inoculated with probiotic constituted by BB-12 (Bifidobacterium.) to assess growth and prebiotic supplement sources carbon in order to encourage their development and stability over time. Initially we proceeded to activate the microorganism comprising a commercial strain of pure culture of BB-12 in lyophilized state, incubating 1 g. in 99 mL of culture in Man Rogosa and Sharpe broth (MRS), which was supplemented with 0.05% (w / v) L-Cysteine as an essential source of nitrogen to reduce the potential for oxide reduction means (strict anaerobic conditions required ). The experimental units were made up of 24 samples of 20 g. of commercial brand royal jelly raspberry flavor, combinations were obtained through a mix design using the Simplex-Grid STATGRAPHICS Plus version 8.0 software. The results of the statistical analysis made it possible to determine the optimal combinations of probiotic in which the BB-12 has a less than 106 CFU / g. concentration prerequisite for the functional food to be considered, so the dilutions 105 and 107 reflected values between 1,45x107 to 4,9x107 CFU / ml. . Finally, the presence of BB-12 in the colonies obtained through a Gram stain was confirmed, which was evident on amount and form satisfactorily.
Keywords: Functional food, probiotics, prebiotics, gelatin and simplex grid.